Concentric versus eccentric cycling at equal power output or effort perception: Neuromuscular alterations and muscle pain - Clos, P.; Mater, A.; Laroche, D.; Lepers, R. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study aimed to compare neuromuscular alterations and perceptions of effort and muscle pain induced by concentric and eccentric cycling performed at the same power output or effort perception. Fifteen participants completed three 30-min sessions: one in concentric at 60% peak power output (CON) and two in eccentric, at the same power output (ECCPOWER) or same perceived effort (ECCEFFORT). Muscle pain, perception of effort, oxygen uptake as well as rectus femoris and vastus lateralis electromyographic activities were collected when pedaling. The knee extensors maximal voluntary contraction (MVC) torque, the torque evoked by double stimulations at 100 Hz and 10 Hz (Dt100; Dt10), and the voluntary activation level (VAL) were evaluated before and after exercise. Power output was higher in ECCEFFORT than CON (89.1 ± 23.3% peak power). Muscle pain and effort perception were greater in CON than ECCPOWER (p < 0.03) while muscle pain was similar in CON and ECCEFFORT (p > 0.43). MVC torque, Dt100, and VAL dropped in all conditions (p < 0.04). MVC torque (p < 0.001) and the Dt10/ Dt100 ratio declined further in ECCEFFORT (p < 0.001). Eccentric cycling perceived as difficult as concentric cycling caused similar muscle pain but more MVC torque decrease. A given power output induced lower perceptions of pain and effort in eccentric than in concentric yet similar MVC torque decline. While neural impairments were similar in all conditions, eccentric cycling seemed to alter excitation-contraction coupling. Clinicians should thus be cautious when setting eccentric cycling intensity based on effort perception.